Coordinated Translocation of Presequence-Containing Precursor Proteins Across Two Mitochondrial Membranes: Knowns and Unknowns of How TOM and TIM23 Complexes Cooperate With Each Other - Genge, Marcel G.; Mokranjac, Dejana (Frontiers in Physiology, 2022)
The vast majority of mitochondrial proteins are encoded in the nuclear genome and synthesized on cytosolic ribosomes as precursor proteins with specific mitochondrial targeting signals. Mitochondrial targeting signals are very diverse, however, about 70% of mitochondrial proteins carry cleavable, N-terminal extensions called presequences. These amphipathic helices with one positively charged and one hydrophobic surface target proteins to the mitochondrial matrix with the help of the TOM and TIM23 complexes in the outer and inner membranes, respectively. Translocation of proteins across the two mitochondrial membranes does not take place independently of each other. Rather, in the intermembrane space, where the two complexes meet, components of the TOM and TIM23 complexes form an intricate network of protein-protein interactions that mediates initially transfer of presequences and then of the entire precursor proteins from the outer to the inner mitochondrial membrane. In this Mini Review, we summarize our current understanding of how the TOM and TIM23 complexes cooperate with each other and highlight some of the future goals and unresolved questions in the field.